A sustainable model for enhancing road quality with recycled plastic bags - Gulseven, Osman; Shaimaa Ashkanani; Sarah Abdullah; Hawraa Ismaeil; Haneen Alkandari; Mariam Baroun (Kuwait Journal of Science, 2019)
Plastic waste disposal is becoming a serious challenge to all major metropolitan municipalities around the world. If not disposed of properly, the plastic wastes can degrade the environment for several years. In this article, we propose recycling plastic bags as an input in road construction process can improve the road properties. Traditionally, residues from petroleum distillation called bitumen are used in road surfacing and coating. Here, we test the hypothesis that mixing shredded plastic with bitumen in an optimal ratio can enhance the road quality by improving the strength and durability of the asphalt. In order to find out the optimal percentage of plastic content, we applied Marshall stability, retained strength, and stripping tests using a variety of bitumen mixtures with different plastic mix ratios. Our results revealed that the bitumen mixture with 8% recycled plastic ratio is the most durable and strongest mixture with the highest scores from all tests.